A termografia no auxílio do diagnóstico complementar no câncer de tireoide - Camargo, Viviane Magas Bittencourt de (2020)
Thyroid cancer is a pathology that has an increasing incidence and affects mainly women. In recent decades, incidence rates have steadily increased and it is estimated that thyroid cancer will become the fourth most common type of cancer by the year 2030. The diagnosis is made from palpation of the nodule, ultrasound and fine needle aspiration (FNAB). The ultrasound exam often presents a false positive diagnosis leading the individual to perform unnecessary biopsies in addition to generating a psychological impact resulting from a false positive diagnosis.To analyze the thermal behavior of nodules in patients with thyroid cancer using infrared thermography using a cold stress protocol. This is an exploratory descriptive study carried out in partnership with Hospital Erasto Gaertner. The study included 33 individuals of legal age; who were diagnosed with cancer in the thyroid region, totaling 42 nodules, 11 malignant and 31 benign. The images were collected in the pre-stress period (t-1) and post-stress in the cold (t0) every 30 seconds over a period of 10 minutes. The measures of temporal assessment of neoplastic and healthy tissues were based on the number of pixels in each current time period. Longitudinal analysis was used to assess the thermal behavior of tumors over time. Software R was established for the analysis of data extracted from the analyzed regions. Results: In the descriptive analysis of the sample, it was found that there was a predominance of being female (79.7%) and the average age of all those who participated in the research was 54.7 years. The effectiveness of ultrasound in identifying cancers of the thyroid gland was evaluated, considering the gold standard of FNAP as the standard, with no known sensitivity values for malignant cancer of 0.82 and for benign cancer of 0.52. Based on the analysis of median minimum, average and maximum tissue temperatures, the control group showed higher peaks (31.23 ° C) than the study group (30.98 ° C). The difference in the thermal behavior of tumor tissues was evidenced by longitudinal analysis. It is possible to verify that the beginning of tissue heating is highly significant (p = 0.001) for comparison of tumors. Another relevant aspect in the differentiation of tumor tissues for an analysis of the variability of the “well” effect, which occurred in the period t-1 until the period t3’. Benign tumors have a variational ratio of 1,816 compared to malignant tumors, being significant for p-value = 0.001. Benign tumors have a different thermal behavior from malignant tumors and both have a different behavior from normal tissue. The fixed model proposed for longitudinal analysis shows that as time progresses, the number of the pixels tends to increase. It was noted that benign and malignant tissues behave differently in terms of vascular recovery.